2018
DOI: 10.1165/rcmb.2017-0141oc
|View full text |Cite
|
Sign up to set email alerts
|

The Splicing Factor hnRNPA1 Regulates Alternate Splicing of the MYLK Gene

Abstract: Profound lung vascular permeability is a cardinal feature of acute respiratory distress syndrome (ARDS) and ventilator-induced lung injury (VILI), two syndromes known to centrally involve the nonmuscle isoform of myosin light chain kinase (nmMLCK) in vascular barrier dysregulation. Two main splice variants, nmMLCK1 and nmMLCK2, are well represented in human lung endothelial cells and encoded by MYLK, and they differ only in the presence of exon 11 in nmMLCK1, which contains critical phosphorylation sites (Y an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
4
7
0
Order By: Relevance
“…The moxifloxacin treatment increased the amount of SRSF1 splicing factor in SMA fibroblasts, which affected the CASP9 exon cassette splice‐in; however, the effect on the inclusion of MAPT exon 10 was mild (Figure A,B). hnRNPA1 inhibits the inclusion of INSR exon 11 and promotes skipping of MYLK exon 11 . The reduced levels of hnRNPA1 after moxifloxacin treatment increased the inclusion of MYLK exon 11 as expected; however, in the case of the INSR splicing, the effect was significant and dose‐dependent but in contrast to the anticipated result (Figure C,D).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The moxifloxacin treatment increased the amount of SRSF1 splicing factor in SMA fibroblasts, which affected the CASP9 exon cassette splice‐in; however, the effect on the inclusion of MAPT exon 10 was mild (Figure A,B). hnRNPA1 inhibits the inclusion of INSR exon 11 and promotes skipping of MYLK exon 11 . The reduced levels of hnRNPA1 after moxifloxacin treatment increased the inclusion of MYLK exon 11 as expected; however, in the case of the INSR splicing, the effect was significant and dose‐dependent but in contrast to the anticipated result (Figure C,D).…”
Section: Resultssupporting
confidence: 55%
“…hnRNPA1 inhibits the inclusion of INSR exon 11 43 and promotes skipping of MYLK exon 11. 44 The reduced levels of hnRNPA1 after moxifloxacin treatment increased the inclusion of MYLK exon 11 as expected; however, in the case of the INSR splicing, the effect was significant and dose-dependent but in contrast to the anticipated result ( Figure 8C,D). This can be caused by different cell lines than the one used in the original study, or more factors are implicated in the INSR exon 11 splicing.…”
Section: Moxifloxacin Treatment Modulates Levels Of Two Main Smn2 Ssupporting
confidence: 66%
“…Because pulmonary epithelial cell stretch is accompanied by increased mechanical stress in airways, cyclic stretch was used to imitate airway mechanical stress by Flex cell Tension System. Related studies showed that 18% elongation was widely applied to human pulmonary artery endothelial cells and pulmonary microvascular endothelial cells in ventilator-induced pulmonary injury [3638]. 12% elongation was applied in airway smooth muscle hypertrophy using Flex cell Tension System [39].…”
Section: Discussionmentioning
confidence: 99%
“…hnRNP A1 belongs to the hnRNP family, a large family of ubiquitously expressed heterogeneous nuclear ribonucleoproteins (hnRNPs) that regulate several aspects of nucleic acid metabolism, including pre-mRNA packing, alternative splicing, and transportation of poly(A) mRNA 14 - 16 . hnRNP expression is altered in many types of cancers 17 .…”
Section: Introductionmentioning
confidence: 99%